Review the Dimensions of Brand Equity (Study on Community of Users of Federal Brand Motorcycle Engine Lubricants in Sampit Early 2021) - Sutejo, Bambang; Mulyanto, Sigit (Universitas Darwan Ali, 2021)
This study aims to determine how the strength of the brand equity of Federal brand motorcycle engine lubricants is seen from the dimensions of brand awareness, brand associations, perceived quality, and brand loyalty. The population in this study is the community of users of Federal brand motorcycle engine lubricants who replace lubricants at a motorcycle repair shop in Sampit. Data was obtained by using a questionnaire which was then analyzed by descriptive analysis. Brand awareness data is measured by percentage calculation, brand association data is measured by the Cochran test, while data on perceived quality and brand loyalty is measured by means. The results of the study show that (1) the dimension of brand awareness of Federal motorcycle lubricants ranks third in the top of mind, second in brand recall, and 4% in brand recognition. Associations related to Federal lubricants are Astra products, lubricants whose quality is tested, durable, and easy to obtain because they are available in various places in Indonesia. Federal lubricant quality perception has a performance level (3.12) lower than the importance level (4.25). From the switcher level brand loyalty to liking the brand, is categorized as good enough as the committed buyer level, it can be seen from the frequency of consumers suggesting and promoting Federal lubricants (3.91), therefore it can be concluded that Federal lubricant brand equity is quite strong.